Nano-Bio Probe Design and Its Application for Biochemical Analysis - Ye, Bang-Ce.; Zhang, Min.; Yin, Bin-Cheng.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
In this volume, Prof. Ye and his coworkers propose and review the concept of nano-bio probe design for biochemical analysis on the basis of their recent published works. A unique biochemical analysis technology based on fluorescence polarization enhanced by nanoparticles is described here with successful applications in environmental monitoring, rapid and sensitive sensing protease activity and high-throughput screening of inhibitors. Furthermore, they introduce a versatile molecular beacon (MB)-like probe for the multiplex sensing of targets such as sequence-specific DNA, protein, metal ions and small molecule compounds based on the self-assembled biomolecule-graphene conjugates. Besides, some colorimetric and luminescence probes utilizing metal nanoparticles for biochemical applications are also presented, such as chiral enantiomer discrimination and separation, environmental monitoring, clinic diagnosis and etc.
Introduction -- Nanomaterial-Enhanced Fluorescence Polarization and Its Application -- Versatile Graphene-Based Nano-Bio Probe Design and Its Appliction -- Metal Nanoparticles-Based Colorimetric Probe Design and Its Application -- Metal Nanoclusters-Based Luminescent Probe Design and Its Application.
Keywords: Biochemical engineering; Nanotechnology; Biochemistry; Nanoscale science; Nanoscience; Nanostructures; Biochemical Engineering; Nanotechnology; Biochemistry, general; Nanoscale Science and Technology